LIMITS OF REFORM AND COLONIAL KAZAKH INTEGRATION: RURAL MULLAH ELECTIONS, THE ORENBURG ASSEMBLY, AND THE MUFTIATE QUESTION IN AKMOLINSK PROVINCE (1868–1905) - Kudaibergen, Yersultan (Nazarbayev University School of Sciences and Humanities, 2025)
This study examines the contested politics of mullah appointments in Akmolinsk Province between 1868 and 1905 to analyze how Russian imperial policies of Russification and peasant colonization marginalized rural Kazakh communities. Employing Bradley Parker’s theory of colonial negotiation and Amanda Lagji’s “waiting room” model, it argues that imperial reforms—while promising integration—produced administrative fragmentation and legal ambiguity, fostering isolation and weakening traditional Islamic authority. Drawing on petitions, inspection reports, and reform proposals, the study reveals that mullah elections became arenas of legal contestation and communal agency. Far from passive subjects, Kazakh communities engaged imperial law to assert competing claims of local legitimacy. Yet this engagement was fractured: Kazakhs were divided among themselves, with rival factions seeking imperial endorsement of their preferred religious leaders. Meanwhile, imperial officials—confronted with the visible disintegration of rural order—struggled to articulate a consistent policy on Islam. Their responses oscillated between conservative desires for stability, reformist impulses, and deep anxieties over Islamic revivalism and political loyalty. Urban Muslim elites such as Shaymerden Koshegulov advocated for a Kazakh Muftiate to assert religious autonomy, while others resisted any expansion of clerical authority. Imperial actors, wary of provoking unrest or empowering independent Islamic institutions, delayed or dismissed most initiatives. These competing visions revealed the limits of colonial governance and the contradictions of Russia’s modernizing claims. Ultimately, the politics of mullah appointments expose a fractured colonial landscape—where legal ambiguity, bureaucratic inertia, and ideological tension shaped the struggle over authority and belonging in the Kazakh Steppe.
Keywords: Russian Empire; Central Asia; Akmolinsk Province; Colonial Reforms; Islamic Communities; Orenburg Muslim Spiritual Assembly; Mullah Elections; Islamic Authority; Kazakh Muftiate; type of access: open access